Mental health of displaced and refugee children resettled in low-income and middle-income countries: risk and protective factors. - Reed, R; Fazel, M; Jones, L; Panter-Brick, C; Stein, A (2012)
Children and adolescents who are forcibly displaced represent almost half the world's internally displaced and refugee populations. We undertook a two-part systematic search and review of the evidence-base for individual, family, community, and societal risk and protective factors for the mental health outcomes of children and adolescents. Here we review data for displacement to low-income and middle-income settings. We draw together the main findings from reports to identify important issues and establish recommendations for future work. We draw attention to exposure to violence as a well established risk factor for poor mental health. We note the paucity of research into predictor variables other than those in the individual domain and the neglect of other variables for the assessment of causal associations, including potential mediators and moderators identifiable in longitudinal work. We conclude with research and policy recommendations to guide the development and assessment of effective interventions.